Entre santos e marranos: a Inquisição portuguesa como instrumento de perseguição étnica aos cristãos-novos (sécs. XVI-XVIII) - Carlos Henrique Alvarenga Urquisa Marques (2022)
This research was developed with the purpose of registering the effects of the ethnic discrimination promoted in Portugal, from the 16th through 18th century, on the inquisitorial procedural system. Dividing the work into three phases, it was first devoted to the historical trajectory of heretical movements in the known West. Then, the formation of the Inquisition was described in relation to its structure, procedural system and ideology, orienting the work especially to the Modern Inquisitions. In the second phase, efforts were initially oriented towards understanding the process of developing an ethnic abjection towards new Christians, based on the cultural heritage received from the Jews. Afterwards, the main ways of expression of the mentality, which was conventionally attributed to the converts, were delimited. In addition, in the third chapter, the reflexes of racial prejudice in the inquisitorial system were explained, demonstrating the commitment of the inquisitorial criminalization processes and the main persecutory institutes with a project of discriminatory social control. In conclusion, the methodological journey undertaken in the investigation was summarized and the legal elements that allowed confirming the ethnically discriminatory immanence of the Portuguese inquisitorial system, in pursuit of the interests of the dominant social strata in Portuguese society, were enumerated.